Reference charts for height and weight of school children from west Malaysia in comparison with the United States centers for disease control and prevention - Bong, Y.B.; Merican, A.F.; Majid, A.M.; Shariff, A.A. (2012)
Background: Reference charts are widely used in healthcare as a screening tool. This study aimed to produce reference growth charts for school children from West Malaysia in comparison with the United States Centers for Disease Control and Prevention (CDC) chart. Methods: A total of 14,360 school children ranging from 7 to 17 years old from six states in West Malaysia were collected. A two-stage stratified random sampling technique was used to recruit the subjects. Curves were adjusted using Cole's LMS method. The LOWESS method was used to smooth the data. Results: The means and standard deviations for height and weight for both genders are presented. The results showed good agreement with growth patterns in other countries, i.e., males tend to be taller and heavier than females for most age groups. Height and weight of females reached a plateau at 17 years of age; however, males were still growing at this age. The growth charts for West Malaysian school children were compared with the CDC 2000 growth charts for school children in the United States. Conclusion: The height and weight for males and females at the start of school-going ages were almost similar. The comparison between the growth charts from this study and the CDC 2000 growth charts indicated that the growth patterns of West Malaysian school children have improved, although the height and weight of American school children were higher than those for West Malaysian school children.